Analisis Hukum Islam terhadap Perkawinan Sirri di Ketegan, Sepanjang, Sidoarjo - Muflikhatul Khoiroh; Imron Mustofa; Mila Rosyidah (State Islamic University (UIN) of Sunan Ampel, 2022)
This research is based on the unregistered marriages phenomenon in Ketegan, Sepanjang, Sidorajo. Marriage is considered as an instant solution to juvenile delinquency, which has the potential to be promiscuous. There are two issues to be confirmed through this research: first, the attitude or response of the people in Ketegan to the practice of unregistered marriage that has taken place in their environment; Second, critical analysis of the phenomenon of unregistered Marriage on Islamic law’s perspective. This is field research, with a critical analysis method of data obtained. The data was collected through interviews with subjects, their parents, and several community leaders who had direct contact with them. This research found two conclusions: first, the people of Ketegan Village don’t seem to care about this kind of marriage. This is influenced by the variety of Ketegan people's mindsets and various tribes, majority of Madurese. However, peoples' view on unregistered marriages are mostly strained by problems threatening family honor. Second, The Islamic law analysis concludes unregistered marriage as illegal for not complying with the provisions of Law no. 1 of 1974 about marriage. This marriage potentially causes the rights and mate to be unfulfilled. In short, unregistered marriage has the potential to create injustice, contrary to the most fundamental principle of Islamic law, justice (al-'adālah).